1991
DOI: 10.1111/j.1476-5381.1991.tb09786.x
|View full text |Cite
|
Sign up to set email alerts
|

A calcium channel antagonist stereoselectively decreases ethanol withdrawal hyperexcitability but not that due to bicuculline, in hippocampal slices

Abstract: 1 Extracellular recordings were made from CA1 area of isolated hippocampal slices of the mouse after chronic ethanol administration in vivo, with orthodromic stimulation of the Schaffer collateral/ commissural fibres. 2 The (+)-isomer of the calcium channel antagonist PN 200-110 (isradipine) significantly decreased all the recorded signs of hyperexcitability in the slices during ethanol withdrawal. These included increased paired pulse potentiation and decreases in the thresholds for elicitation of single and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

1992
1992
2003
2003

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(15 citation statements)
references
References 29 publications
2
13
0
Order By: Relevance
“…Intracellular calcium concentration is significantly enhanced after chronic in vitro exposure to ethanol. The enhancement is consistent with an increased number of NMDA receptors through which calcium can enter neurons, whereas calcium channel antagonist can attenuate the ethanol withdrawal hyperexcitability in hippocampus [143]. During the chronic dependent state, glutamate release is decreased; conversely, uptake and tissue concentration of glutamate are increased [54,79].…”
Section: Neurochemical Effects Of Alcohol On Glutamatergic Transmissionmentioning
confidence: 64%
“…Intracellular calcium concentration is significantly enhanced after chronic in vitro exposure to ethanol. The enhancement is consistent with an increased number of NMDA receptors through which calcium can enter neurons, whereas calcium channel antagonist can attenuate the ethanol withdrawal hyperexcitability in hippocampus [143]. During the chronic dependent state, glutamate release is decreased; conversely, uptake and tissue concentration of glutamate are increased [54,79].…”
Section: Neurochemical Effects Of Alcohol On Glutamatergic Transmissionmentioning
confidence: 64%
“…The neuronal mechanisms are likely to be complex given the multiple actions of ethanol in the central nervous system and the fact that these systems may be (and often are) altered by the history of ethanol exposure. For example, chronic exposure to ethanol results in an upregulation of NMDA receptors (Grant, 1990;Liljequist, 1991;Hoffman and Tabakoff, 1994) and an upregulation in the density of voltage-dependent calcium channels (Messing et al, 1986;Dolin et al, 1987;Dolin and Little, 1989;Whittington and Little, 1991). More recently, Rasmussen et al (2002) has reported that mediobasal hypothalamus pro-opiomelanocortin (POMC) mRNA concentrations were decreased after chronic ethanol consumption.…”
Section: Discussionmentioning
confidence: 99%
“…Their work suggests that acamprosate acts as a 'partial coagonist' at the NMDA receptor, such that low concentrations enhance activation when receptor activity is low, and high concentrations inhibit activation when receptor activity is high. This may be particularly relevant to the success of acamprosate as a pharmacotherapy given that chronic exposure to ethanol results in an upregulation of NMDA receptors (Grant, 1990;Liljequist, 1991;Hoffman and Tabakoff, 1994) and an upregulation in the density of voltage-dependent calcium channels (Messing et al, 1986;Dolin et al, 1987;Dolin and Little, 1989;Whittington and Little, 1991). Acamprosate also promotes the release of taurine in the brain (Dahchour and de Witte, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…This effect was stereoselective and was seen with the doses of drug that were required to displace radiolabelled dihydropyridines from CNS binding sites in vivo (Supervilai & Karobath, 1984). We have demonstrated that ethanol withdrawal hyperexcitability occurs in the isolated hippocampal slices in vitro ; this was prevented by the dihydropyridine calcium channel antagonist, PN 200-1 10, in a selective and stereospecific manner (Whittington & Little, 1991).…”
Section: Introductionmentioning
confidence: 99%